Zastosowanie metody ELECTRE III w ocenie spójności społeczno-ekonomicznej regionów Unii Europejskiej w latach 1995-2003 - Jahn, Joanna (Method ELECTRE III as a Tool for Estimation of Social and economic Cohesion of European Union's Regions between 1995 and 2003, 2008)
The main aim of this paper is analyzing economic and social cohesion in the European Union in the context of regional economic growth achievements between 1995 and 2003. 129 regions at NUTS 1 and NUTS 2 level were chosen to carry out detailed analyses. The Ward's method is used in order to group similar regions. The variables which are correlated with regional GDP per capita are tested using Principal Component Analysis (PCA). The results of PCA are taken into account in the regions ranking. Then the multi-criteria method ELECTRE III is used by the author to classify the regions according to their economic and social achievements.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 115-139